Analysis of The Interrelationship of Human Resource Performance, Digital Service Quality, Perceived of Service Value and Customer Loyalty - Karyono, Karyono; Violin, Vivid; Osman, Isnawati; Gusti Rao, Don; Apramilda, Riesna (Malikussaleh University, Aceh, Indonesia, 2024)
The purpose of this study is to evaluate the comparison of customer loyalty levels between conventional travel agents and travel agents that use digital strategies in their business processes. This study uses a descriptive and quantitative approach. Data collection methods use surveys and snowball sampling techniques. The results of the study indicate that there is a significant difference in the level of customer loyalty between conventional and online travel agents. Conventional travel agent consumers tend to be more loyal because they receive direct interaction with travel agency managers, customers also get direct service from staff, this direct service and interaction have been shown to increase customer satisfaction and loyalty. Online travel agent consumers are more price sensitive and have lower loyalty levels, even though they choose to use digital services considering effectiveness and efficiency factors. The conclusion of the study is that conventional travel agency consumers prefer personalized services and direct interaction with service providers, while online travel agency consumers prioritize price and have considerations for access to reviews in determining travel agents. Researchers suggest that management design an effective strategy to combine conventional and digital activities in the business process and services provided to customers, conventional travel agents must continue to emphasize direct interactions that have been well established and excellent, while online agents must improve customization elements and customer service to increase loyalty.